Improving Mathematics Learning Outcomes of Third-Grade Students on the Material of Calculating the Perimeter and Area of Flat Buildings through the STAD Type Cooperative Learning Model - Rosfiani, Okta; Nuraini, Tri; Turiskia, Fitra; Khairunnisa, Hafidzah; Sholeh, Hafidz Qurnia (PT. Riset Press International, 2024)
The background of this study is based on the results of observations of third grade students of SDN Kuningan Barat 03 Pagi who have low learning outcomes or have not reached the KKM in Mathematics material on calculating the perimeter and area of flat shapes (square and rectangle). The purpose of this study was to improve learning outcomes in Mathematics lessons for third grade students on the perimeter and area of flat shapes at SDN Kuningan Barat 03 Pagi. This research uses a class action research method with a cycle system consisting of planning, implementation, observation, and reflection. The subjects used in this study were third grade students totaling 24 students consisting of 12 boys and 12 girls with different ability backgrounds. The results obtained in the pre-cycle with 45.83% completeness and in cycle I 66.67% while in cycle 2 there was an increase in learning outcomes, namely with 91.67% completeness. The conclusion of this study is that learning by using the STAD type cooperative learning model can improve the learning outcomes of third grade Mathematics students on the material of calculating the perimeter and area of flat shapes at SDN Kuningan Barat 03 Pagi.